What Is the Specificity of Classical Mathematics?. (11th April 2017) - Priest, Graham
Abstract : This paper addresses the question of what is distinctive about classical mathematics. The answer given is that it depends on a certain notion of conditionality, which is best understood as telling us something about the structure of the mathematics in question, and not something about the logical particle 'if'.